Introduction - Yang Mayer, Siena College, USA, Chingyen (Asiatic: IIUM Journal of English Language and Literature, 2015)
In the early spring of 2014 just when Mother Nature was waking up from an unusually long Upstate New York winter dormancy, an invitation to guest-edit a special issue of Asiatic: IIUM Journal of English Language and Literature on Asian American literature came from its Editor-in-Chief Dr. Mohammad A. Quayum. I was greatly honoured by the kind invitation as I know Dr. Quayum is an internationally renowned prolific writer, leading literary critic, passionate educator and an unsurpassed translator of major literary works by Bengali writers. For the next couple of weeks, I was musing over a suitable topic for the special issue, one that would not only reflect the vibrancy of Asian American literature but also the positionality of my life as an Asian American.